Institutional Measures for Supporting OER in Higher Education: An International Case-Based Study - Marín, Victoria I.; Zawacki-Richter, Olaf; Aydin, Cengiz H.; Bedenlier, Svenja; Bond, Melissa; Bozkurt, Aras; Conrad, Dianne; Jung, Insung; ondakci, Yasar; Prinsloo, Paul; Roberts, Jennifer; Veletsianos, George; et al. (Open Education Studies, 2022)
Open Educational Resources (OER) in higher education cannot be put into practice without considering institutional contexts, which differ not only globally but also within the same country. Each institutional context provides educators with opportunities or limitations where Open Educational Practices (OEP) and OER for teaching and learning are involved. As part of a broader research project, and as a follow-up to national perspectives, an international comparison was conducted, based on institutional cases of nine different higher education systems (Australia, Canada, China, Germany, Japan, South Africa, South Korea, Spain, Turkey). Aspects regarding the availability of infrastructure and institutional policies for OER, as well as the existence of measures directed at OER quality assurance and at the promotion of the development and use of OER were covered. The resulting theoretical contribution sheds light on an international comparative view of OER and points towards country-specific trends, as well as differences among institutions. These aspects could provide an impetus for the development of institutional guidelines and measures. In line with international literature on the topic, recommendations are derived to promote/ enhance the use of OER in teaching and learning in higher education at the institutional level.
CRIS-Team Scopus Importer:2022-09-30
Keywords: faculty development; Higher education institutions; institutional policies; international case-based study; open educational resources (OER)